KORELASI KETERAMPILAN MEMBACA PEMAHAMAN TEKS EKSPOSISI DENGAN KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS X SMK NEGERI 9 PADANG - Mangalandong, Maya Sri; Abdurahman, Abdurahman; Ratna, Ellya (Universitas Negeri Padang, 2018)
ABSTRACTÂ This article was written to find the correlation between Reading comprehension skills of exposition texts with writing skills in writing exposition texts. The data of this research was score of reading test of exposition text and score of writing test of exposition texts. The data were obtained by using two types of tests. They were multiple choices to measure the skills of reading comprehension of exposition texts and performance tests to measure writing skills in writing exposition texts. Based on the results of data analysis and the discussions, there were three things found. First, the average score of intermediate reading comprehension of Exposition text by grade X SMK Negeri Padang 9 were qualified good (80.84). Second, the average score of writing skills text exposition class X students of SMK Negeri Padang 9 were at good qualifications (80.00). Third, there was a significant correlation between the skills of reading comprehension of exposition text with writing skills in writing exposition texts done byÂ the students of grade X SMK Negeri Padang which was at significant levels 9 95% with dk = n-1. Based on t-test hyphothesis, the results were accepted because t calculate > t table, 4.52 > 1.67.Â Kata kunci: korelasi ,keterampilan, membaca, pemahaman, menulis, teks eksposisi